How the Public in the US Responded to Javanese and Balinese Performing Arts? - Rafngi Mufidah; Dhanang Respati Puguh; Singgih Tri Sulistiyono (Diponegoro University, 2021)
After declared independent, Indonesia had to deal with the question of its national identity. It was pertaining to the debate on the national culture, particularly arts. As Indonesia had diverse traditional arts, the debate was a dilemma. Many people disagreed if the traditional arts became the national identity. Meanwhile, Indonesian traditional arts, especially Javanese and Balinese ones, had been appreciated abroad. During Sukarno's regime, Indonesia sent several art missions to present itself to the world. They performed mostly traditional arts from several regions, including Java and Bali. By employing the historical method, this study aims to discuss Javanese and Balinese performing arts shows in the United States. It is of importance that from 1950s to 1960s, Indonesia had to adapt to the Cold War, which forced the developing countries to choose the Western or Eastern bloc in their foreign policy. Until the beginning of the 1960s, Indonesia tended to be with the Eastern bloc. Subsequently, there was a tendency to be with the other bloc. Therefore, in this article the response to the Javanese and Balinese performing arts shows in the US after two eras was analyze.